Globalization and the Inequality of Nations. - Krugman, P; Venables, A (CEPR, 1994)
The paper considers a model in which an imperfectly competitive manufacturing sector produces goods which are used both for final consumption and as intermediates. Intermediate usage creates cost and demand linkages between firms and a tendency for manufacturing agglomeration. How does globalization affect the location of manufacturing and the gains from trade? At high transport costs all countries have some manufacturing industry, but when transport costs fall below a critical value a core-periphery pattern forms spontaneously, and nations that find themselves in the periphery suffer a decline in real income. As transport costs continue to fall there comes a second stage of convergence in real incomes, in which the peripheral nations gain and the core nations may well lose.